An unusual cause of inspiratory stridor in the newborn: congenital pharyngeal teratoma – a case report. Issue 1 (December 2016) - Posod, Anna; Griesmaier, Elke; Brunner, Andrea; Pototschnig, Claus; Trawöger, Rudolf; Kiechl-Kohlendorfer, Ursula
Abstract Background Neonatal inspiratory stridor is an important examination finding that requires immediate and adequate evaluation of the underlying etiology. Depending on the severity of the airway obstruction and the presence or absence of associated symptoms such as respiratory distress and feeding problems, early initiation of a complete diagnostic workup can be crucial. The most common cause of neonatal inspiratory stridor is laryngomalacia, however, several differential diagnoses need to be investigated. More rare causes include oral or laryngeal masses. Teratomas of the head and neck region are one of the most unusual causes of respiratory distress during the neonatal period. We present a case of a mature teratoma in the oropharynx presenting with airway obstruction in a newborn infant. Case presentation A four-day-old female Caucasian infant was admitted to the neonatal intensive care unit of our hospital because of inspiratory stridor and profound desaturations while feeding. Diagnostic workup by ultrasound, magnetic resonance imaging and flexible endoscopy revealed a pediculated lesion in the pharyngeal region causing intermittent complete airway obstruction. The mass was surgically removed by transoral laser resection on the seventh day of life. Histological evaluation was consistent with a mature teratoma without any signs of malignancy. The further hospital course was uneventful, routine follow-up examinations at 3, 6 and 9 months of age showed no evidence of tumor recurrence. Conclusion Neonatal stridor is a frequent symptom in the neonatal period and is mostly caused by non-life-threatening pathologies. On rare occasions, however, the underlying conditions are more critical. A careful stepwise diagnostic investigation to rule out these conditions, to identify rare causes and to initiate early treatment is therefore warranted.